Application of bayesian techniques for the identification of accident-prone road sections (2014)
The use of Bayesian techniques for the identification of accident-prone road sections has become very important in recent years. The objective of this investigation consisted of identifying accident-prone road sections in the Municipality of Ocaña (Colombia) using the Bayesian Method (BM); the modeling approach developed involved the creation of a database of accidents that occurred between the years 2007 (January) and 2013 (August) and the application of the methodology on 15 sections of urban road. The final analyses show that the BM is an original and fast tool that is easily implemented, it provides results in which 4 accident-prone or dangerous road sections were identified and ranked them in order of danger, establishing a danger ranking that provides a prioritization for investments and the implementation of preventive and/or corrective policies that will maximize benefits associated with road safety.